Case Study On Talisman Energy, A Major International Oil & Gas Producer - Nging, Go Eng (2004)
This case study took a closer look at the oil and gas industry in general. It then focused on Talisman Energy and its operations in Malaysia. Case analysis on the Company was carried out using Social, Economy, Politic and Technology (SEPT), Michael Porter's Five Competitive forces, SWOT (Strengths, weaknesses, Opportunities and Threats) analysis and financial ratio analysis. It further explored the alternative strategies and recommendations for the Company.